(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1939)
Report on excavations in 1936 and 1937. The unusual rectangular form of the fort was dictated by the space available. Features examined included the rampart, ditch and intervallum and the east gateway. All the internal features (principia, praetorium, granaries, barracks, ovens) were examined and evidence was found to suggest that the fort had been deliberately dismantled. Artefacts included an unbroken sword from a foundation trench of the principia.